Economic analysis of the 'Take Charge' intervention for people following stroke: Results from a randomised trial. (February 2022) - Te Ao, Braden; Harwood, Matire; Fu, Vivian; Weatherall, Mark; McPherson, Kathryn; Taylor, William J; McRae, Anna; Thomson, Tom; Gommans, John; Green, Geoff; Ranta, Annemarei; Hanger, Carl; et al.
Objective: To undertake an economic analysis of the Take Charge intervention as part of the Taking Charge after Stroke (TaCAS) study. Design: An open, parallel-group, randomised trial comparing active and control interventions with blinded outcome assessment Setting: Community. Participants: Adults ( n = 400) discharged to community, non-institutional living following acute stroke. Interventions: The Take Charge intervention, a strengths based, self-directed rehabilitation intervention, in two doses (one or two sessions), and a control intervention (no Take Charge sessions). Measures: The cost per quality-adjusted life year (QALY) saved for the period between randomisation (always post hospital discharge) and 12 months following acute stroke. QALYs were calculated from the EuroQol-5D-5L. Costs of stroke-related and non-health care were obtained by questionnaire, hospital records and the New Zealand Ministry of Health. Results: One-year post hospital discharge cost of care was mean (95% CI) $US4706 (3758–6014) for the Take Charge intervention group and $6118 (4350–8005) for control, mean (95% CI) difference $ −1412 (−3553 to +729). Health utility scores were mean (95% CI) 0.75 (0.73–0.77) for Take Charge and 0.71 (0.67–0.75) for control, mean (95% CI) difference 0.04 (0.0–0.08). Cost per QALY gained for the Take Charge intervention was $US −35, 296 (=£ −25, 524, € −30, 019). Sensitivity analyses confirm Take Charge is cost-effective, even at a very low willingness-to-pay threshold. With a threshold of $US5000 per QALY, the probability that Take Charge is cost-effective is 99%. Conclusion: Take Charge is cost-effective and probably cost saving.